Food use is affected by the experience of nest predation: implications for indirect predator effects on clutch size - Zanette, Liana Y.; Hobson, Keith A.; Clinchy, Michael; Travers, Marc; Williams, Tony D. (Oecologia, 2013)
Indirect predator effects on prey demography include any effect not attributable to direct killing and can be mediated by perceived predation risk. Though perceived predation risk clearly affects foraging, few studies have yet demonstrated that it can chronically alter food intake to an extent that affects demography. Recent studies have used stable isotopes to gauge such chronic effects. We previously reported an indirect predator effect on the size of subsequent clutches laid by song sparrows (Melospiza melodia). Females that experienced frequent experimental nest predation laid smaller clutches and were in poorer physiological condition compared to females not subject to nest predation. Every female was provided with unlimited supplemental food that had a distinctive ¹³C signature. Here, we report that frequent nest predation females had lower blood δ¹³C values, suggesting that the experience of nest predation caused them to eat less supplemental food. Females that ate less food gained less fat and were in poorer physiological condition, consistent with the effect on food use contributing to the indirect predator effect on clutch size. Tissue δ¹⁵N values corroborated that clutch size was not likely constrained by endogenous resources. Finally, we report that the process of egg production evidently affects egg δ¹³C values, and this may mask the source of nutrients to eggs. Our results indicate that perceived predation risk may impose food limitation on prey even where food is unlimited and such predator-induced food limitation ought to be added to direct killing when considering the total effect of predators on prey numbers.